Building Purchase Decisions For Fashion Products in E-Commerce: The Role Of Social Media Endorsers, Viral Marketing, And Perceived Quality - Lilis Purwitasari; Hesti Respatiningsih; Dewi Shanti Nugrahani (International Forum of Researchers and Lecturers, 2025)
The purpose of this study was to see how social media endorsements, viral advertising, and perceived quality can build Shopee consumers' decisions in Purworejo Regency to buy fashion products in e-commerce. We conducted data analysis using regression, t-test, and F-test on a sample of 107 respondents. The results showed that social media endorser and viral marketing variables had a positive and significant effect on purchase decisions, while perceived quality did not show a significant positive impact. These findings highlight the importance of marketing strategies that incorporate social media endorsers and viral marketing in influencing consumer purchase decisions. This research provides valuable insights for marketers in designing effective campaigns for fashion products on e-commerce platforms.